Inflammatory mediators as surrogates of malignancy - Mohammad Sohail Asghar; Mohammad Zohaib Asghar; Aima Zahid; Hafiz Syed Zaigham Ali Shah; Khan, Hamna; Hammad Zia (Journal of the Pakistan Medical Association, 2022)
Inflammation related to cancer occurs in the cellular vicinity of the tumour and is involved with predictions related to the course of disease and survival prognosis in varioua malignancies. These inflammatory markers affect different phases of tumourigenesis, i.e. carcinogenesis, tumour expansion, lymphovascular invasion, and distant metastasis, and, as a result, tumour cells can activate immune mediators and cells directly and/or chemokines as well as prostaglandins. Numbers of circulating different blood cells, i.e. lymphocytes, platelets, neutrophils and levels of plasma proteins, like C-reactive protein and interleukins that are components of inflammatory responses, are hallmarks of pathways leading to tumourigenesis. Thus, they can provide vital information in stratifying patients according to the risk and precisely targeted clinical care and outcome in malignancies. —Continue